PEMANFAATAN SERASAH MANGROVE Rhizopora sp SEBAGAI BIOSORBEN UNTUK SORPSI LIMBAH - Mia Azizah; Mamay Maslahat; Luqman Maulana (Forestry Study Program University Of Mataram, 2019)
Litter mangrove contains elements lignin-selulosa that can be adsorb heavy metal so that it can be modified into biosorben. Batik industry an industry that potentially produce waste containing heavy metal so that it can be caused damage environment .One of a breed of metal the polluter high priority found in sewage batik industry is lead. The purpose of this research to make use of litter mangrove as biosorben adsorption metal lead and applied on waste batik industry to adsorption metal lead . The condition steady adsorption lead by biosorben litter mangrove happened to pH 3 , contact time 30 minutes and weights biosorben 0.5 gram. Litter mangrove can be used as biosorben capable of absorbing metal lead of batik industry with capacity adsorption 0,6025 µg / g with efficiency adsorption 100 %. Isoterm adsoprsi lead by biosorben litter mangrove following a pattern isoterm freundlich assuming that happens adsorption physics form a multilayer worth regression 0,9213 but type isoterm langmuir having value regression less similar namely 0,9114.